(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article analyzes the role of national cultural centers operating in the Republic of Uzbekistan in society and their role in ensuring inter-ethnic harmony. Uzbekistan is a multinational state in which representatives of different nationalities and ethnic groups live in harmony. National cultural centers, in addition to preserving the culture, traditions and language of these nationalities and ethnic groups, and promoting their active participation in social life, serve to strengthen the atmosphere of mutual respect and cooperation in society. The article covers the areas of activity of these centers, their contribution to ensuring inter-ethnic stability and the support measures provided by the state. The importance of national cultural centers in preserving national values ​​and unifying society is also widely analyzed.